The dynamics of radicalization: a relational and comparative perspective - Alimi, Eitan Y. (Oxford Univ. Press, 2015)
"The book comparatively investigates the processes of radicalization, focusing on questions of how and when such processes unfold, rather than on why they happen in the first place. Alimi, Bosi, and Demetriou argue that processes of radicalization develop primarily through the interplay of three specific mechanisms: "competition for power" among movement actors; "threat/opportunity spirals" between the movement and its political environment; and "outbidding" between movement actors and state security forces. Each arena or mechanism affects and is affected by the other two, creating a multilayered pathway of radicalization. Using the "most different case" logic, the authors argue their theory through three case studies: the Red Brigades in Italy (1968-1980), the Greek Cypriot Enosis-EOKA (1945-1960), and the Al Qaeda/Sunni-led Salafi Transnational Jihad Movement (1984-2001). Without losing sight of the significant differences between the cases, or of the way in which they influence the particular sequence of the process, the book provides an empirically proven and widely applicable analytic framework for understanding how political processes and different contexts drive radicalization"--